Isolation of bacterial agents from the lungs of cattle with pneumonia and detection of Pasteurella spp. by polymerase chain reaction - Kiliç, A; Muz, A (Tubitak Scientific & Technological Research Council Turkey, 2004)
Lungs from 8222 cattle slaughtered at an abattoir in Elazig were examined macroscopically, and pneumonia was detected in 500 (6.1%) lungs. These samples were inoculated onto blood agar supplemented with 7% sheep blood for isolation of bacterial agents. A polymerase chain reaction (PCR) based upon the use of species-specific primers was carried out on DNA samples extracted from suspected Pasteurella spp. isolates. In addition, a mouse inoculation test was carried out on suspected Pasteurella multocida isolates. A total of 311 (62.2%) bacterial agents were isolated from the lung samples and were identified as 7.2% Staphylococcus aureus, 6% Pasteurella multocida, 6% Corynebacterium spp., 5.8% yeast, 3.8% Streptococcus spp, 3.6% Staph-Vlococcus epidermidis, 2.6% Escherichia coli, 2.2% Bacillus spp., 2% Pseudomonas spp., 1.8% Mannheimia haemolytica, 1.6% Actinobacillus spp., 1.2% Klebsiella spp., 0.2% Moraxella spp., 0.2% Proteus spp., and 18% mixed bacteria. Twenty-four (80%) of the Pasteurella multocida isolates were positive in the mouse inoculation test in cattle. All P. multocida and M. haemolytica strains that were positive by culture were also found to be positive by PCR. However, toxigenic Pasteurella multocida was not detected in any isolates by PCR using primers derived from the toxA gene.
Pnömonili si?ir akci?erlerinden bakteri i?zolasyonlari ve i?zole pasteurella'larin polimeraz zincir reaksiyonu i?le saptanmasi
Keywords: pneumonia; cattle; Pasteurella multocida; Mannheimia haernolytica; polymerase chain reaction (PCR); culture